Interação e discurso oral: questões de aquisição de linguagem e de letramento emergente - Rojo, Roxane Helena Rodrigues (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The purpose of this paper is to question the statements of universality of interactional practices and mechanisms in the culture, as are usually found in emergent literacy and language acquisition literature. To do this, I will analyse and discuss practices in two different familiar interactional contexts, which differs in terms of their level of literacy (high and low). Results show that interactional processes and mechanisms vary depending on social practices of particular group and cultures.